A pre-series prototype for the superconducting undulator afterburner for the European XFEL. Issue 1 (1st December 2022) - Casalbuoni, S.; Baader, J.; Geloni, G.; Grattoni, V.; Decking, W.; La Civita, D.; Lechner, C.; Lilje, L.; Liu, S.; Marchetti, B.; Potter, A.; Schneidmiller, E.; et al.
Abstract: We propose to develop, characterize and operate a superconducting undulator (SCU) afterburner consisting of 5 undulator modules (1 module = 2 SCU coils of 2 m length and 1 phase shifter) plus a pre-series prototype at the SASE2 hard X-ray beamline of European XFEL. This afterburner will produce an output in the order of 10 10 ph/pulse at photon energies above 30 keV. The project is divided into the production of a pre-series prototype module and a small-series production of 5 modules. Central goals of this R&D activity are: the demonstration of the functionality of SCUs at an X-ray FEL, the set up of the needed infrastructure to characterize and operate SCUs, the industrialization of such undulators, and the reduction of the price per module. In this contribution, the main parameters and specifications of the pre-series prototype module are described.